Efficiency and Effectiveness Analysis of Village Financial Management (VFM) (Case Study Asahan Regency) - Siagian, Bukit Buchori; Maryunani, Maryunani; Sakti, Rahmad Krishna; Santoso, Dwi Budi (International Journal of Social and Local Economic Governance, 2016)
As an implementation of decentralized development, village financial management (VFM) is a financing model in a way to closer the needs of development at the village level. Theoretically, the successful objectives achievement of this authority delegation is if VFM can be done efficiently and effectively. This study aimed to analyze these efficiency and effectiveness of VFM and analyze factors inhibiting. The results showed that 1) VFM in Asahan district has not implemented both efficiently and effectively that shown from the weak implementation of both good governance principles and continuous improvement and, 2) Factors inhibiting the efficiency and effectiveness of VFM are, (i) lack of musrenbang transparency specifically the quality of information, access to information, the transparency mechanism of information and the level of information disclosure, (ii) lack of budgeting transparency, in particular the level of information disclosure, access to information and quality of information, (iii) lack of supervision transparency in particular the level of transparency, information quality and information access, (iv) the weak of oversight participation, especially the satisfaction level of participation and involve the community, and (v) lack of monitoring accountability in particular public complaints mechanism, access to the audit report and the responsibility structure.